Neuropsychological Functioning and Quality of Life Among Type 2 Diabetic Patients in Ghana - Sarfo, J.O. (University of Ghana, 2013)
Diabetes as a metabolic disorder predisposes patients to both biomedical and psychological dysfunctions. The aim of the study was to determine the pattern of neuropsychological deficits and quality of life among individuals living with Type 2 diabetes mellitus in Ghana. One hundred (100) participants comprising 50 patients with Type 2 diabetes and 50 healthy controls matched on age and education were recruited. Using a battery of neuropsychological tests and behavioural measures, data was collected at the Diabetic Clinic, Korle-Bu Teaching Hospital. The results showed that individuals with Type 2 diabetes obtained significantly lower scores than the healthy controls on executive functions, memory, visuospatial and visuoconstructional functioning tests. In addition, Type 2 diabetes also affected the quality of life of diabetic patients who were sampled for the study. Specifically, depression, complications, anxiety, age of respondents, health beliefs, cognitive failure, interpersonal sensitivity and hostility predicted quality of life. These results have implications for clinical management and research design in psychological studies involving Type 2 diabetes.
Thesis (MPHIL)-University of Ghana, 2013